Distribution of Cheyletus mites in dust samples. Issue 1 (31st December 2022) - Zhou, Y.; Zhu, X.; Ren, Y.; Hui, Y.
Abstract: Cheyletus, including Cheyletus malaccensis and Cheyletus eruditus and other species, is a predatory mite at genus level. Some studies have reported distribution rates of Cheyletus in dust samples, but their results are inconsistent. The aim of this meta analysis was to comprehensively evaluate the distribution rates of Cheyletus in dust samples. Articles concerning the distribution rates of Cheyletus species in dust samples were searched and screened in electronic databases. The pooled distribution rate with 95% confidence interval (95% CI) were calculated. Thirteen articles were included in this meta-analysis. A total of 15 studies reported the rates of Cheyletus in all mites from dust and the pooled rate was 2.62% (95% CI: 2.32%–2.92%). A total of three studies reported the rates of dust samples with Cheyletus in all dust samples and their pooled rate was 19.82% (95% CI: 5.10%–34.54%). Heterogeneities existed within included studies and source of heterogeneities could not be found though subgroup analyses by species, publication year, sample size of all mites were conducted. There is a low rate of Cheyletus in all mites from dust and a low rate of dust samples with Cheyletus in all dust samples.